Product of sugar-free banana similar to jam: development and characterization, sensory, physicochemical, and microbiological - BERNARDI, Daniela Miotto; AGUIAR, Maryelle Cristina Souza; LIMA, Romilda De Souza; SILVESTRO, Mariana Feldberg; KUMMER, Laura; MARTINS, Jefferson Kramin; LUCAS, Maísa; LUFT, Camila Luiza; PERUSSO, Fernanda; GONÇALVES-TENORIO, Andiara; HENNING, Katiana; KERSCHER, Elaine Januaria; et al. (Food Science and Technology, 2024)
Banana is a fruit widely produced and consumed, and its processing in the form of jams can be an alternative to improve its use. Jams of fruit, sugar free, are a market trend and can be important foods for schoolchildren. The objective was to develop a sugar-free banana product, similar to jam, and evaluate their acceptability, composition, and microbiological and sensory stability. Three formulations were developed using banana, lemon juice, cinnamon, and cocoa, which were stored at an average temperature of 25°C for up to 2 months. The acceptability of the products was evaluated by 102 consumers, and 8 trained evaluators were also selected to carry out the quantitative descriptive analysis (QDA). The QDA and microbiological (Salmonella spp., Escherichia coli, molds, and yeasts) parameters were analyzed on the day of production and two months after manufacturing. There was no statistical difference between the three formulations for all sensorial attributes evaluated, and the average scores indicated excellent acceptability. The results of the microbiological and QDA analyses indicated that during storage, the formulations were stabilized. Thus, it was possible to develop, with simple technology, sugar-free banana products, similar to jam, with good acceptability and acceptable microbiological parameters.